Trauma exposure, PTSD symptoms, and tobacco use: Does church attendance buffer negative effects?. Issue 7 (13th August 2020) - Mathew, Amanda R.; Yang, Eric; Avery, Elizabeth F.; Crane, Melissa M.; Lange‐Maia, Brittney S.; Lynch, Elizabeth B.
Abstract: Traumatic stress and posttraumatic stress disorder (PTSD) are overrepresented in urban African American communities, and associated with health risk behaviors such as tobacco use. Support and resources provided by churches may reduce trauma‐related health risks. In the current study, we assessed weekly church attendance as a moderator of relations between (a) traumatic event exposure and probable PTSD, and (b) probable PTSD and tobacco use. Data were drawn from a health surveillance study conducted in seven churches located in Chicago's West Side. Participants ( N  = 1015) were adults from churches as well as the surrounding community. Trauma exposure was reported by 62% of participants, with 25% of those who experienced trauma reporting probable PTSD. Overall, more than one‐third of participants (37.2%) reported current tobacco use. As compared with non‐weekly church attendance, weekly church attendance was associated with a lower likelihood of PTSD (odds ratio [OR] = 0.41; 95% confidence interval [CI] = 0.26–0.62; p  < .0001) and lower tobacco use overall (OR = 0.22; 95% CI = 0.16–0.30; p  < .0001), but did not moderate the effect of trauma exposure on risk of PTSD, or the effect of PTSD on tobacco use. Findings support church attendance as a potential buffer of trauma‐related stress.